The role of pepsinogen test among the patients with gastric cancer. - AL-Robeyii, Mahmood R.; AL-Robeyii, Mahmood R.; AL-Khayli, Nahla G.; AL-Mousawy, Kalida (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Identification the relationship of pepsinogen test (pepsinogenI and I /pepsinogen II ratio) and gastric cancer patients make the gastric cancer early diagnosed and prolong the life surviving rate.Patients and Methods: Serum pepsinogen I and pepsinogen II (PG I and PG I / PG II ratio) measured in 50 patients with gastric cancer ,30 gastritis patients diagnosed , and 16 healthy control by using enzyme immunoassay in those study groups, and the results of PG I and PG I / PG II ratio were comparing to 50 gastric cancer patients whom diagnosed histopathologically according the stomach regions, while the gastritis patients diagnosed endoscopically.Results: This study showed that the age of patients with gastric carcinoma range between 25 and 80 years with mean age of 47.5 in females and 66.5 years in males(P=0.004). Immunologically, this study revealed that the serum pepsinogen I level was reduced less than 70nmg/dl and it was detected in 37(74%, P=0.008), 17(56.6%) and 5(31.2) in gastric carcinomatose patients, gastritis patients and healthy control respectively. While PG I /PG II ratio was found < 3 in 34(68%, P=0.007) of the stomach cancer patients, 15(50%) in patients control and 4(25%) in healthy control. In this study there is a high prevalence of positive result of PGI (89.1%, P=0.00 highly significant) in corpus-fundus region of stomach as compared to PGI/PGII ratio(44.12%, P=0.493).This study showed that the PGI is more sensitive (74%),and more accuracy (72.72%)than PG I /PG II ratio,while it is more specific (75%) than PGI.Conclusion: Pepsinogen I and pepsinogen II (PGI and PG I / PG II ratio) are useful as non-invasive method for diagnosis of the precancerous diseases in the stomach, and it is sensitive and specific test, but it did not precisely reflect disease dissemination and pathological type. Gastric cancer was significantly high in age group 45-65 years.